Aplicabilidad de las adaptaciones curriculares en la enseñanza de operaciones matemáticas básicas, en los estudiantes con discapacidad intelectual del colegio de bachillerato 27 de febrero de la ciudad de Loja, período lectivo 2017-2018. - Granda Sanchez, Alyson Nicole (2019)
The curricular adaptations constitute "a box of tools", guidelines, recommendations and contributions related to the development of inclusive actions, which contribute to the reduction of organizational, attitudinal, pedagogical and classroom barriers, for which purpose and with the purpose of contributing in the teacher preparation for the realization of the curricular adaptations in the teaching of the operations of the basic mathematics of the students with intellectual disability of the Bachillerato School "27 de Febrero" of the City of Loja. The present study of scientific research type is carried out with a quantitative and qualitative approach and is analyzed through the methods, scientific, descriptive, analytical-synthetic, deductive, inductive and statistical; the instruments used were the survey for teachers and parents, the planning model for curricular adaptation, the pedagogical test of the third year of basic education. The sample had 6 students with intellectual disabilities, a representative of DECE NN, 6 parents, and 7 teachers of mathematics, in the latter it was possible to identify difficulties such as not knowing how to make curricular adaptations, stating that they were not trained, lacking methodologies, didactic and technological resources for the development of the inclusive process of the students with intellectual disability, reason for which the workshop was developed to prepare the teachers in the realization of the curricular adaptations for the teaching of the basic mathematical operations with what was achieved awareness and knowledge about how to carry out a curricular adaptation, so that they can subsequently apply in their lesson plans, and continuous training in the realization of curricular adaptations is recommended for an adequate inclusive education.